2017
DOI: 10.11604/pamj.2017.26.10.11368
|View full text |Cite
|
Sign up to set email alerts
|

Profil étiologique des anémies dans un service de médecine interne

Abstract: L'anémie constitue un problème majeur de la santé publique à travers le monde malgré l'amélioration remarquable des conditions de vie. Elle est classée par l'OMS comme l'un des dix problèmes les plus sérieux du monde. Notre objectif est de décrire les profils épidémiologique et étiologique des cas d'anémies prises en charge dans notre formation. Il s'agit d'une étude rétrospective menée durant 5 ans, allant de Janvier 2011 à décembre 2015 et portant sur 150 patients. L'âge moyen de nos patients est de 48,8ans … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…El Hioui et al [5] found a male predominance of 42 women and 40 men. For Ali Zinebi et al [7] the female predominance was noted in 62.37% with a sex ratio of 1.78. According to Momar C. [7] and Penda B.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…El Hioui et al [5] found a male predominance of 42 women and 40 men. For Ali Zinebi et al [7] the female predominance was noted in 62.37% with a sex ratio of 1.78. According to Momar C. [7] and Penda B.…”
Section: Discussionmentioning
confidence: 92%
“…For Ali Zinebi et al [7] the female predominance was noted in 62.37% with a sex ratio of 1.78. According to Momar C. [7] and Penda B. [8] the sex ratio was 0.720 and 0.96.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations